Financial strategy for successful management of minikitchen restaurant using cash flow management - H. Umar (Sean Institute, 2024)
Effective cash flow management enables restaurants to guarantee the availability of adequate funds for day-to-day operations and prospective business expansion; therefore, the administration of Minikitchen restaurants utilizing cash flow management requires a financial strategy. This research employs qualitative methodologies to assist Minikitchen Restaurant in the implementation of strategies for revenue management, appropriate pricing, SWOT analysis, and meticulous inventory management. The findings indicated that financial strategies such as preparing a realistic financial budget, effectively managing cash flow, enhancing financial management knowledge and skills, establishing a competitive advantage, and adjusting to changes in the digital age can all contribute to the success of Minikitchen restaurant management.